Fortification of blackcurrant juice with crowberry : impact on polyphenol composition, urinary phenolic metabolites, and postprandial glycemic response in healthy subjects - Törrönen, Riitta; McDougal, Gordon J.; Dobson, Gary; Stewart, Derek; Hellström, Jarkko; Mattila, Pirjo; Pihlava, Juha-Matti; Koskela, Ali; Karjalainen, Reijo (Journal of Functional Foods, 2012)
v 2012 ok